Improving Arm Muscle Power in Basketball Through TRX Suspension Training - Alen Rismayadi; Hasya Natawijaya; Nina Sutresna; Dadan Mulyana; Geraldi Novian (International Journal of Basketball Studies, 2023)
One of the important physical components in the game of basketball is power, which can be achieved by using the muscles ability to produce maximum strength in a short time. The aim of this study was to determine the effect of TRX suspension exercises on increasing arm muscle strength in basketball. The method used is an experiment using the One-Group Pretest-Posttest Design. This research was conducted on UPI women's basketball UKM athletes with the total sampling method. The data collection technique was carried out by conducting a pre-test on 15 people as samples. The instrument used to measure the power ability of the arm muscles is the two-hand medicine ball put test. After that, the samples were given the TRX suspension training treatment. Then carry out the post-test using the instrument for the two-hand medicine ball put test. The data analysis technique uses parametric statistics with normal and homogeneous-oriented samples. The results of the hypothesis test stated that T count was greater than T table, meaning that the research hypothesis was accepted, specifically that TRX suspension training exercises had a significant effect on arm muscle power. The research recommendation is that TRX suspension training exercises can be used as an alternative to train arm muscle power.